Statistical analysis of sub-zero temperature effects on fatigue strength of welded joints - Braun, Moritz (Welding in the World, 2022)
Ships and offshore structures in Arctic environments are exposed to severe environmental actions and sub-zero temperatures. Thus, the design of such structures has to account for the Arctic environment and must be cost-efficient at the same time. A vital part of the design process is to ensure that fatigue-induced failure does not occur in the lifetime of the structure. While effects of high temperatures on material behavior are well covered in international standards and guidelines, there is no comprehensive guidance for sub-zero temperature fatigue strength assessment. Additionally, stress-life (S–N) test data of welded joints at sub-zero temperatures is particularly scarce. Hence, this study presents an extensive review of recent test results of various weld details tested in the range of − 50 to 20 °C. This data could build the basis for future considerations of temperature effects in fatigue design guidelines and recommendations. For this purpose, the fatigue test results are submitted to a rigorous statistically assessment—including a summary of the limitations of current design guidelines with respect to sub-zero temperature effects.